THE EFFECIVENESS OF COGNITIVE TRAININGS IN OLDER ADULTS – REVIEW - Matysiak, Olga; Brzezicka, Aneta (Studia Psychologica: Theoria et praxis, 2017)
There is a gradual increase in the number of elderly people living in the world. Also, human aging is associated with a deterioration of cognitive processes, that touches multiple domains, including memory, attention, processing speed and cognitive control. For this reason, intervention programs that improve the intellectual functioning of older citizens became very popular. One of the broadly discussed approach aims to support the elderly’s functioning with the usage of cognitive trainings. Although, emerged training regimes are considered by some researchers to be effective, they are systematically criticized by others. Possible causes are due to a diversity of approaches to the training design itself, to the way it is applied, as well as to the training methodology. In terms of their utility, it is crucial to decide which interventions are effective, how strongly they affect behavior, and to what extent they actually transfer to everyday life of older participants. Especially the last attribute should be e ential, considering participants’ well-being. Therefore, this article aims not only to systematize reports on improving the cognitive functioning of the elderly, but above all to draw attention to the increasingly perceptible problem of verification of the training effects of seniors. We would like to emphasize the need for implementation a stronger methodological unification of cognitive trainings, that allows a fair assessment of their impact on the quality of life of the participating seniors.